Answer:
Why is 3 x 1/10 less than 3 x 10
Since is 3 x 1/10 = 3/10 and
3 × 10 = 30, and
30 > 3/10
Step-by-step explanation:
Hello there!
<u><em>Answer: ⇒⇒=1975</em></u>
_______________________________________________________
Step-by-step explanation:
First you had to multiply by the number.
![395*5=1975](https://tex.z-dn.net/?f=395%2A5%3D1975)
1975 is the right answer.
___________________________________________________________
Hope this helps!
Thank you for posting your question at here on brainly.
Have a great day!
-Charlie
______________________________________________________________
Y = x + 1
y = 2x - 1
basically we r going to sub in one y for another
x + 1 = 2x - 1
1 + 1 = 2x - x
2 = x
now we sub 2 in for x in either of the original equations to find y
y = x + 1
y = 2 + 1
y = 3
so ur solution is (2,3)
![\text{The sum of } 1\frac{7}{10} \text{ and } 3\frac{3}{5} \text{ is } 5\frac{3}{10}](https://tex.z-dn.net/?f=%5Ctext%7BThe%20sum%20of%20%7D%201%5Cfrac%7B7%7D%7B10%7D%20%20%5Ctext%7B%20and%20%7D%203%5Cfrac%7B3%7D%7B5%7D%20%5Ctext%7B%20is%20%7D%205%5Cfrac%7B3%7D%7B10%7D)
<em><u>Solution:</u></em>
Given that we have to find the sum of ![1\frac{7}{10} \text{ and } 3\frac{3}{5}](https://tex.z-dn.net/?f=1%5Cfrac%7B7%7D%7B10%7D%20%5Ctext%7B%20and%20%7D%203%5Cfrac%7B3%7D%7B5%7D)
<em><u>Let us first convert the mixed fractions to improper fractions</u></em>
Multiply the whole number part by the fraction's denominator.
Add that to the numerator.
Then write the result on top of the denominator
Therefore,
![1\frac{7}{10} = \frac{10 \times 1 + 7}{10} = \frac{10+7}{10} = \frac{17}{10}\\\\3\frac{3}{5} = \frac{5 \times 3 + 3}{5} = \frac{18}{5}](https://tex.z-dn.net/?f=1%5Cfrac%7B7%7D%7B10%7D%20%3D%20%5Cfrac%7B10%20%5Ctimes%201%20%2B%207%7D%7B10%7D%20%3D%20%5Cfrac%7B10%2B7%7D%7B10%7D%20%3D%20%5Cfrac%7B17%7D%7B10%7D%5C%5C%5C%5C3%5Cfrac%7B3%7D%7B5%7D%20%3D%20%5Cfrac%7B5%20%5Ctimes%203%20%2B%203%7D%7B5%7D%20%3D%20%5Cfrac%7B18%7D%7B5%7D)
Now we can add both the fractions
![1\frac{7}{10} + 3\frac{3}{5} = \frac{17}{10} + \frac{18}{5}](https://tex.z-dn.net/?f=1%5Cfrac%7B7%7D%7B10%7D%20%2B%203%5Cfrac%7B3%7D%7B5%7D%20%3D%20%5Cfrac%7B17%7D%7B10%7D%20%2B%20%5Cfrac%7B18%7D%7B5%7D)
Make the denominators same
![1\frac{7}{10} + 3\frac{3}{5} = \frac{17}{10} + \frac{18 \times 2}{5 \times 2}\\\\1\frac{7}{10} + 3\frac{3}{5} = \frac{17}{10} + \frac{36}{10}\\\\\text{Add the fractions since the denominator is same }\\\\1\frac{7}{10} + 3\frac{3}{5} = \frac{17+36}{10} = \frac{53}{10}](https://tex.z-dn.net/?f=1%5Cfrac%7B7%7D%7B10%7D%20%2B%203%5Cfrac%7B3%7D%7B5%7D%20%3D%20%5Cfrac%7B17%7D%7B10%7D%20%2B%20%5Cfrac%7B18%20%5Ctimes%202%7D%7B5%20%5Ctimes%202%7D%5C%5C%5C%5C1%5Cfrac%7B7%7D%7B10%7D%20%2B%203%5Cfrac%7B3%7D%7B5%7D%20%3D%20%5Cfrac%7B17%7D%7B10%7D%20%2B%20%5Cfrac%7B36%7D%7B10%7D%5C%5C%5C%5C%5Ctext%7BAdd%20the%20fractions%20since%20the%20denominator%20is%20same%20%7D%5C%5C%5C%5C1%5Cfrac%7B7%7D%7B10%7D%20%2B%203%5Cfrac%7B3%7D%7B5%7D%20%3D%20%5Cfrac%7B17%2B36%7D%7B10%7D%20%3D%20%5Cfrac%7B53%7D%7B10%7D)
Now convert the fraction to mixed number
When we divide 53 by 10 , the remainder is 3
Therefore, write 5 as a whole number and and 3 as numerator and 10 as denominator
![\frac{53}{10} = 5\frac{3}{10}](https://tex.z-dn.net/?f=%5Cfrac%7B53%7D%7B10%7D%20%3D%205%5Cfrac%7B3%7D%7B10%7D)
Thus the sum of given mixed fraction is ![5\frac{3}{10}](https://tex.z-dn.net/?f=5%5Cfrac%7B3%7D%7B10%7D)